Território, Paisagem e Fragmento: análise multiescalar das dinâmicas de supressão regular e irregular de vegetação nativa no estado de São Paulo - Gavioli, Felipe Rosafa (2024)
Combating illegal deforestation is a priority for society and governments, aiming to reduce greenhouse gas emissions and conserve biodiversity. Command and control actions take place in a complex manner and are carried out by environmental licensing entities within an institutional arrangement that encompasses a broad legislative apparatus for the protection of native vegetation remnants. One of the aspects of this protective apparatus is the rule established for the regular suppression of vegetation, which, however, is little studied. Knowing the characteristics of the legal suppression of native vegetation can help identify problems and propose improvements in the fiscalization and licensing ecosystem. The present study is part of this context and evaluated the dynamics of regular and irregular suppression in the state of São Paulo between 2009 and 2020, using a multi-scale approach. First, we analyze the processes of regular suppression, fiscalized irregular suppression, unfiscalized irregular suppression and regeneration of native vegetation in the territory of São Paulo, considering a municipal scale, and exploring the factors that induce these processes, using geographic data processing and multiple linear regressions. We found that legal suppression of native vegetation in the state corresponded to only 1.31% of the total suppressed between 2009 and 2020, and fiscalized suppression accounted for 11.14% of the total, meaning that 87.55% of the area of suppressed native vegetation is illegal and not fiscalized. The predominant dynamic in the state is the net regeneration of native vegetation, with 229 thousand hectares regenerated during the study period. The Cerrado presented a more worrying situation of illegal suppression, which reached around 3% of the biome's area in the state during the period studied. Regular suppression is linked to the urban-industrial development of municipalities, while unfiscalized irregular suppression is linked to the availability of road access, gentle slopes and warmer locations. The irregular suppression monitored was related to the percentage of native vegetation coverage in the municipalities and the extension of the municipalities. Then, the study focused on the regular suppressions through Authorizations for the Suppression of Native Vegetation (ASVs), analyzing the insertion of those ASVs in a landscape, considered as a radius buffer surrounding the coordinate point of the ASV. Geospatial and statistical analyzes were carried out on a landscape scale. The regular suppression of native vegetation in São Paulo is marked by small areas, of vegetation in pioneer and initial stages of regeneration, and for urban, agricultural and public works purposes. From a geographical point of view, regular suppression is concentrated in the São Paulo macro-metropolis region. Was identified an important relationship between landscape attributes and the regeneration stage of the ASV vegetation, with earlier stages occurring in more anthropic landscapes, better served by road access and with lower slopes. Based on the results obtained, improvements are suggested in government actions to combat illegal deforestation, as well as point out proposals for future studies. The results obtained can help in understanding the drivers of native vegetation suppression in the state, which contributes to the constant improvement of public forest management, management and conservation policies.